The Efficacy of Vitamin C on Postoperative Outcomes after Posterior Lumbar Interbody Fusion: A Randomized, Placebo-Controlled Trial - Lee, Gun Woo; Yang, Han Seok; Yeom, Jin S.; Ahn, Myun-Whan (Clinics in orthopedic surgery, 2017)
Vitamin C has critical features relavant to postoperative pain management and functional improvement; however, no study has yet evaluated the effectiveness of vitamin C on improving the surgical outcomes for spine pathologies. Thus, this study aimed to explore the impact of vitamin C on postoperative outcomes after single-level posterior lumbar interbody fusion (PLIF) for lumbar spinal stenosis in prospectively randomized design. We conducted a 1-year prospective, randomized, placebo-controlled, double-blind study to evaluate the impact of vitamin C on the postoperative outcomes after PLIF surgery. A total of 123 eligible patients were randomly assigned to either group A (62 patients with vitamin C) or group B (61 patients with placebo). Patient follow-up was continued for at least 1 year after surgery. The primary outcome measure was pain intensity in the lower back using a visual analogue scale. The secondary outcome measures were: (1) the clinical outcome assessed using the Oswestry Disability Index (ODI); (2) the fusion rate assessed using dynamic radiographs and computed tomography scans; and (3) complications. Pain intensity in the lower back was significantly improved in both groups compared with preoperative pain intensity, but no significant difference was observed between the 2 groups over the follow-up period. The ODI score of group A at the third postoperative month was significantly higher than the score of group B. After the sixth postoperative month, the ODI score of group A was slightly higher than the score of group B; however, this difference was not significant. The fusion rates at 1 year after surgery and the complication rates were not significantly different between the 2 groups. Postoperative pain intensity, the primary outcome measure, was not significantly different at 1 year after surgery between the 2 groups. However, vitamin C may be associated with improving functional status after PLIF surgery, especially during the first 3 postoperative months.